Effect of Photobiomodulation on Pain Following Single Visit Non-surgical Root Canal Treatment of Molar Teeth with Symptomatic Irreversible Pulpitis - Narges Farhad-Mollashahi; Eshagh Ali Saberi; Bita Aramesh; Farnaz Faramarzian (Association of Support to Oral Health Research (APESB), 2023)
Objective: To assess the effect of Photobiomodulation (PBM) on post-endodontic pain of mandibular molar teeth with symptomatic irreversible pulpitis. Material and Methods: In this clinical trial, mandibular molars with symptomatic irreversible pulpitis underwent primary endodontic treatment in 90 systemically healthy patients. After root canal treatment, the patients were randomly divided into two groups of PBM with diode laser at 940 nm wavelength and 200 mW output power and placebo (mock PBM therapy). Level of pain was recorded at 6, 12, 24, 48, and 72 hours postoperatively using a visual analog scale (VAS). The data were analyzed using the Mann-Whitney test and the Kruskal-Wallis test. Results: The results showed that post-endodontic pain at all time points was significantly lower in the PBM group compared with the placebo group. The pain score in the PBM group was significantly lower than the placebo group (p<0.05). However, this difference was not significant at 48 h (p=0.18) and 72 h (p=0.12) postoperatively. Also, the results showed that the mean pain score in males and females in the PBM group was significantly lower than in males and females in the placebo group. Conclusion: Photobiomodulation can effectively decrease post-endodontic pain in mandibular molar teeth with symptomatic irreversible pulpitis.